To art or not to art? That is the communal question! - Quirós, Oscar E. (2015)
Southwestern Costa Rica comprises an area of over 8500 km2 and a population of less than 200 000 inhabitants, divided into 27 districts that vary in size and population. Although there is a high level of interest in all forms of art, there is not a single art centre or even a hall with a stage for local talent, with the exception of the San Vito district. JUDESUR, the regional funding agency, is willing to support the construction of local art centres, provided each theatre can continue operating independently. Thisstudy attempts to determine which districts have the best conditions to establish and continue operating an “Arts Centre” on a sustainable manner. To achieve this objective, it is necessary to use a modified market feasibility study that relies on statistical tools. Thus, we took the approach of using more socio-economic metrics and various qualitative measurements as the basic data. Both census and convenience survey data are analysed using the principal component analysis to determine their condition and relative position in comparison to the San Vito district. The results suggest that only a few districtshave the socio-economic conditions and community interest to support a local arts centre.